LncRNA FOXD2‐AS1 as a competitive endogenous RNA against miR‐150‐5p reverses resistance to sorafenib in hepatocellular carcinoma. Issue 9 (18th June 2019) - Sui, Chengjun; Dong, Zhitao; Yang, Cheng; Zhang, Minfeng; Dai, Binghua; Geng, Li; Lu, Jiongjiong; Yang, Jiamei; Xu, Minhui
Abstract: The current study elucidated the role of a long non‐coding RNA (lncRNA), FOXD2‐AS1, in the pathogenesis of hepatocellular carcinoma (HCC) and the regulatory mechanism underlying FOXD2‐AS1/miR‐150‐5p/transmembrane protein 9 (TMEM9) signalling in HCC. Microarray analysis was used for preliminary screening of candidate lncRNAs in HCC tissues. qRT‐PCR and Western blot analyses were used to detect the expression of FOXD2‐AS1. Cell proliferation assays, luciferase assay and RNA immunoprecipitation were performed to examine the mechanism by which FOXD2‐AS1 mediates sorafenib resistance in HCC cells. FOXD2‐AS1 and TMEM9 were significantly decreased and miR‐150‐5p was increased in SR‐HepG2 and SR‐HUH7 cells compared with control parental cells. Overexpression of FOXD2‐AS1 increased TMEM9 expression and overcame the resistance of SR‐HepG2 and SR‐HUH7 cells. Conversely, knockdown of FOXD2‐AS1 decreased TMEM9 expression and increased the sensitivity of HepG2 and Huh7 cells to sorafenib. Our data also demonstrated that FOXD2‐AS1 functioned as a sponge for miR‐150‐5p to modulate TMEM9 expression. Taken together, our findings revealed that FOXD2‐AS1 is an important regulator of TMEM9 and contributed to sorafenib resistance. Thus, FOXD2‐AS1 may serve as a therapeutic target against sorafenib resistance in HCC.